(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
It has become vitally crucial to deploy novel mechanisms for funding investment activities in light of the digital transformation of the global economy and the shift to green technology. This study examines the financing of investment activities in Uzbekistan between 2017 to 2024 and finds areas that show promise for progress. The degree of financial market growth and the condition of digital infrastructure have emerged as the most important predictors of the efficiency of investment activities, which have been determined by econometric planning. In order to evaluate the potential for adaptation to national conditions, the experiences of South Korea, the United Arab Emirates, and Singapore were examined. Concepts for an online platform to draw in investments and an ESG-based project evaluation methodology are the outcomes of the study.